1996
DOI: 10.1128/jvi.70.8.5346-5356.1996
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of the herpes simplex virus type 1 immediate-early regulatory protein, ICP27, is responsible for the aberrant localization of ICP0 and mutant forms of ICP4 in ICP4 mutant virus-infected cells

Abstract: ICP0 and ICP4 are immediate-early regulatory proteins of herpes simplex virus type 1. Previous studies by Knipe and Smith demonstrated that these two proteins are characteristically observed in the nuclei of wild-type virus-infected cells but predominantly in the cytoplasms of cells infected with several ICP4 temperaturesensitive (ts) mutant viruses at the nonpermissive temperature (NPT) (D. M. Knipe and J. L. Smith, Mol. Cell. Biol. 6:2371-2381, 1986). Consistent with this observation, it has been shown previ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
0

Year Published

1996
1996
2006
2006

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 46 publications
2
5
0
Order By: Relevance
“…The insets show an enlargement of a nucleus from the larger field. As previously observed (31,81,82), ICP0 accumulated in fine punctate structures at early times (6 h) postinfection (Fig. 8A).…”
Section: Resultssupporting
confidence: 87%
See 2 more Smart Citations
“…The insets show an enlargement of a nucleus from the larger field. As previously observed (31,81,82), ICP0 accumulated in fine punctate structures at early times (6 h) postinfection (Fig. 8A).…”
Section: Resultssupporting
confidence: 87%
“…The formation of large nuclear inclusions correlated with the absence of ICP27. This finding may reflect previous observations that the expression of ICP27 in the absence of ICP4 results in the cytoplasmic localization of ICP0 (81,82). Also of note is the observation that the expression of ICP22 results in the formation of fine granular structures in the nucleus.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…In continuous cell lines, ICP0 accumulated in the cytoplasm later than in primary human fibroblasts. Recently, it has been reported that in Vero cells infected with mutants overproducing ICP27, ICP0 accumulated at 5 h after infection in both nuclei and cytoplasm, whereas in cells infected with the wild-type virus, ICP0 was detected by immunofluorescence in nuclei only (38). It is conceivable that in these studies, overexpression of ICP27 resulted in accelerated accumulation of ICP0 in the cytoplasm of Vero cells.…”
Section: Discussionmentioning
confidence: 93%
“…Normally, ICP4 and ICP0 are found in both the nucleus and the cytoplasm. Infection with ICP27 mutants, however, results in accumulation of ICP0 and ICP4 exclusively in the nucleus (100)(101)(102). Finally, ICP27 is implicated in the posttranslational modifications of ICP0 and ICP4, and it has been suggested that, in the absence of ICP27, ICP4 may not be phosphorylated (65,73).…”
Section: Fig 2 Infection With Uv-irradiated Hsv Does Not Results In mentioning
confidence: 99%